Amudian versus Yabrudian under the rock shelf: A study of two lithic assemblages from Qesem Cave, Israel. (4th April 2016) - Parush, Yoni; Gopher, Avi; Barkai, Ran
Abstract: This paper presents new results of a lithic study of two distinct lithic assemblages from the Qesem Cave "Shelf" area in the northwestern part of the cave – one Yabrudian and one Amudian, both older than 300 ka. The two assemblages exhibit clear stratigraphic relations, the Yabrudian being deposited on top of the Amudian. A detailed techno-typological study of the two assemblages (n = ∼30, 000 artifacts) is presented as well as a comparative analysis between them. The results indicate that the Yabrudian and Amudian of the "Shelf" area are part of the same technological system sharing similar techno-typological features. Differences are mainly at the relative frequency level and in the density of the various elements of the assemblages. These results suggest that the differences between the assemblages might be related to differences in human activities in the different strata of the "Shelf" area using different tool-kits and not to differences in technology or any other cultural conception.